A porphyrin pentamer as a bright emitter for NIR OLEDs. Issue 15 (21st March 2022) - Tejerina, Lara; Rapidis, Alexandros G.; Rickhaus, Michel; Murto, Petri; Genene, Zewdneh; Wang, Ergang; Minotto, Alessandro; Anderson, Harry L.; Cacialli, Franco
Abstract : NIR OLEDs are achieved by blending ethyne-linked zinc(II) porphyrin pentamers into a red-emitting push–pull polymeric host matrix (PIDT-2TPD). We report external quantum efficiencies of 2.0 % with peak emission at 830 nm, confirming the promise of porphyrin oligomers for non-toxic NIR OLEDs. Abstract : The luminescence and electroluminescence of an ethyne-linked zinc(ii ) porphyrin pentamer have been investigated, by testing blends in two different conjugated polymer matrices, at a range of concentrations. The best results were obtained for blends with the conjugated polymer PIDT-2TPD, at a porphyrin loading of 1 wt%. This host matrix was selected because the excellent overlap between its emission spectrum and the low-energy region of the absorption spectrum of the porphyrin oligomer leads to efficient energy transfer. Thin films of this blend exhibit intense fluorescence in the near-infrared (NIR), with a peak emission wavelength of 886 nm and a photoluminescent quantum yield (PLQY) of 27% in the solid state. Light-emitting diodes (LEDs) fabricated with this blend as the emissive layer achieve average external quantum efficiencies (EQE) of 2.0% with peak emission at 830 nm and a turn-on voltage of 1.6 V. This performance is remarkable for a singlet NIR-emitter; 93% of the photons are emitted in the NIR ( λ > 700 nm), indicating that conjugated porphyrin oligomers are promising emitters for non-toxic NIR OLEDs.